Insights into the virulence‐related genes of Edwardsiella tarda isolated from turbot in Europe: genetic homogeneity and evidence for vibrioferrin production. Issue 5 (11th June 2015) - Castro, N; Osorio, C R; Buján, N; Fuentes, J C; Rodríguez, J; Romero, M; Jiménez, C; Toranzo, A E; Magariños, B
Abstract: Edwardsiella tarda has long been known as a pathogen that causes severe economic losses in aquaculture industry. Insights gained on E. tarda pathogenesis may prove useful in the development of new methods for the treatment of infections as well as preventive measures against future outbreaks. In this report, we have established the correlation between the presence of virulence genes, related with three aspects typically involved in bacterial pathogenesis (chondroitinase activity, quorum sensing and siderophore‐mediated ferric uptake systems), in the genome of E. tarda strains isolated from turbot in Europe and their phenotypic traits. A total of 8 genes were tested by PCR for their presence in 73 E. tarda isolates. High homogeneity was observed in the presence/absence pattern of all the strains. Positive results in the amplification of virulence‐related genes were correlated with the detection of chondroitinase activity in agar plates, in vivo AHL production during fish infection and determination of type of siderophore produced by E. tarda . To the best of our knowledge, this is the first study carried out with European strains on potential virulence factors. Furthermore, we demonstrated for the first time that E. tarda produces the siderophore vibrioferrin.